1996
DOI: 10.3109/00365529609051997
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of SF 68 in the Treatment of Acute Diarrhea a Placebo-Controlled Trial

Abstract: Oral bacteriotherapy with SF 68 strain shortens the duration and the severity of diarrhea in adults and represents a safe and effective approach to re-establishing a balanced microbial flora in this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 12 publications
0
37
0
2
Order By: Relevance
“…It is remarkable that enterocin L50A is still active after oxidation at Met 24 but that (1), and Mongolian airag (3). Nevertheless, in some instances (1,3), the experimental masses obtained after the purification of these bacteriocins have differed from the theoretical ones (5,190 Da for enterocin L50A and 5,178 Da for enterocin L50B). We suspect that these discrepancies are due to chemical modifications at Met residues which are likely to complicate the identification of enterocins.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is remarkable that enterocin L50A is still active after oxidation at Met 24 but that (1), and Mongolian airag (3). Nevertheless, in some instances (1,3), the experimental masses obtained after the purification of these bacteriocins have differed from the theoretical ones (5,190 Da for enterocin L50A and 5,178 Da for enterocin L50B). We suspect that these discrepancies are due to chemical modifications at Met residues which are likely to complicate the identification of enterocins.…”
Section: Discussionmentioning
confidence: 94%
“…Enterococci are an essential part of the endogenous gut microbiota of humans and animals, where they are believed to play a key role in the balance of the microbiota, thereby showing great potential as probiotics (2,5). They are also widespread in nature, found in wastewaters, feces, and slurry, as well as in soil and on plants (27), and are thus considered to be indicators for fecal contamination.…”
mentioning
confidence: 99%
“…While heterogeneity in studies is found, one product, Enterococcus LAB SF68, had one end point, diarrhea lasting greater than 4 days, which was combinable and reported in the Cochrane review. Among the four studies with similar product and end point (84)(85)(86)(87), in the probiotic arms With respect to treatment of infectious diarrhea, it is theorized that by enhancing intestinal colonization by specifi c organisms there would be a reduction in the environmental niche for the off ending pathogen through production of acids, hydrogen peroxide, or other anti-microbial substances, increase of mucus production, and gut barrier defense, as well as competition for nutrients or adhesion receptors, antitoxin action, and stimulation of the immune system ( 82 ). In 2010, a Cochrane systematic review was published on the topic of probiotics and treatment of intestinal infection ( 83 ).…”
Section: Recommendationmentioning
confidence: 99%
“…faecium has already been used successfully in human for the treatment of acute diarrheal diseases and prevention of antibiotic-associated diarrhea (Wunderlich et al 1989;Buydens & Debeuckelaere 1996). The probiotic E. faecium HDRsEf1 strain which was separated by our research group has been licensed a China nation patent (Shi et al 2013) and already used as a feed additive for chicken and piglets; the feeding results demonstrate that HDRsEf1 can reduce diarrhea incidence and severity in weaning piglets and regulate the intestinal flora in chicken (Xiao et al 2014;Gong et al 2015), but the mechanism of intestine benefit remains unknown.…”
Section: Introductionmentioning
confidence: 99%